Abbey, market and cemetery: topographical notes on Coupar Angus in Perthshire, with a description of archaeological excavations on glebe land by the parish church - O'Sullivan, Jerry; O'Sullivan, Tanya; Carter, Stephen (Proceedings of the Society of Antiquaries of Scotland, 1996)
A general review of the topography and archaeology of Coupar Angus, particularly the Cistercian Abbey site. Early settlement evidence and cemetery data are noted. There are details of `Soil sample analysis' by Stephen Carter (1062–3), and `Human skeletal remains' by Tanya O'Sullivan (1063). `Appendix 1: modern accounts and images of Coupar Angus' (1065–6), `Appendix 2: primary sources' (1066), and `Appendix 3: finds catalogue' (1067) conclude proceedings.